2014
DOI: 10.1128/mbio.01364-14
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Is Not Merely a Commensal in Commercial Broiler Chickens and Affects Bird Welfare

Abstract: Campylobacter jejuni is the leading cause of bacterial food-borne infection; chicken meat is its main source. C. jejuni is considered commensal in chickens based on experimental models unrepresentative of commercial production. Here we show that the paradigm of Campylobacter commensalism in the chicken is flawed. Through experimental infection of four commercial breeds of broiler chickens, we show that breed has a significant effect on C. jejuni infection and the immune response of the animals, although these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
233
2
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(268 citation statements)
references
References 22 publications
17
233
2
5
Order By: Relevance
“…Although they are colonized by large numbers of Campylobacter organisms (up to 10 9 bacteria/g), chickens usually exhibit no clinical or other adverse effects (402). An interesting study, however, recently showed that C. jejuni infection of some chicken breeds can lead to prolonged inflammation, damage of the gut, and diarrhea (404).…”
Section: Reducing Campylobacter Transmission In Chickensmentioning
confidence: 99%
“…Although they are colonized by large numbers of Campylobacter organisms (up to 10 9 bacteria/g), chickens usually exhibit no clinical or other adverse effects (402). An interesting study, however, recently showed that C. jejuni infection of some chicken breeds can lead to prolonged inflammation, damage of the gut, and diarrhea (404).…”
Section: Reducing Campylobacter Transmission In Chickensmentioning
confidence: 99%
“…We have shown that birds mount a prolonged local inflammatory response to C. jejuni M1 (22), and it may be that some strains, such as C. jejuni 13126, are more susceptible to this prolonged inflammatory response, delaying cecal colonization of the birds with this strain. Alternatively, there may be differences in metabolic capacity that mean some isolates are more adaptable to higher-level colonization and to the range of differences in physical conditions that are found throughout the GI tract, including pH, oxygen tension, levels of bile, mucins, or differences in the resident microbiota.…”
Section: Figmentioning
confidence: 99%
“…Recent reports mention that the chicken-Campylobacter relationship cannot be regarded as commensal. Mucosal damage can occur as a result of a prolonged pro-inflammatory response (Humphrey et al, 2014). Infection with C. jejuni led to the initiation of innate immune responses in the gut that caused an influx of inflammatory cells, including macrophages and heterophils (de Zoete et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of T lymphocyte function in the gastrointestinal tract during C. jejuni infection are very limited, although T cell responses have been shown in the liver during invasive infections (Jennings et al, 2011). One potential criticism of the past work is that many studies used specific-pathogen-free (SPF) chickens with high challenge doses that have only limited relevance to infection in common broiler breeds (Humphrey et al, 2014). However, previous studies have shown that C. jejuni may directly contribute to poor gut health in broilers (Colles et al, 2008;Williams et al, 2013).…”
mentioning
confidence: 99%